Comparison of Productivity and Efficiency of Irrigation Water Consumption in Lands With Traditional Network under Mirab Management and Integrated and Renovated Lands - Mojtaba Mandegari Kohan; Mehdi Zakerinia; Hossein Dehghan (رویکردهای نوین در مهندسی آب و محیط زیست, 2024)
Traditional water distribution with Mirab is effective to a certain extent in the fair distribution of water, but it has limitations in terms of efficiency and productivity. While in modern networks, it is possible to try to optimize the allocation and distribution of water by using advanced technology and infrastructure. Of course, the implementation of a modern irrigation network, despite the high cost of its implementation, does not necessarily mean that it will be successful in the assigned operation, and its performance should be evaluated and analyzed by experts in this matter. water consumption efficiency in two villages of Shahkooh Sofla with traditional irrigation network and Mohammad Abad with renovated irrigation network and integrated lands has been done. The required data in this section included a questionnaire and field measurements of water flow in the network, and finally with the help of these data, the water productivity in the fields was calculated. performance per water volume unit (CPD), and economic productivity indicators, including gross profit per water volume unit (BPD) and net profit per water volume unit (NBPD) were calculated average CPD index in terms of fresh weight, BPD and NPBD in the Shahkooh, 7.54 (kilogram of wet matter per cubic meter), 12425, 10427 (tomans per cubic meter) and in the Mohammad Abad, respectively 0.41 (kilogram of dry matter per cubic meter), 1510 , 918 (tomans per cubic meter) has been obtained. Therefore, in Shahkooh , despite the traditional network of water distribution management, more economic productivity has been achieved